2013
DOI: 10.1177/0004563213488758
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the use of BD Vacutainer® SST II™ and RST™ in general practice: investigation of artefactual hyperkalaemia

Abstract: Background: Current sampling and transport conditions of samples in general practice can result in pseudohyperkalaemia. This study was undertaken to determine, in a general practice setting, whether there is any difference in haemolysis obtained when using BD Vacutainer Õ Rapid Serum Tubes (BD RST) compared with using BD Vacutainer Õ SST TM II Advance Blood Collection Tubes (BD SSTII). Methods: Blood was collected from 353 patients requiring blood sampling who were attending 31 general practitioner practices i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Similarities and differences in the concentration of tested analytes measured in RST have been reported previously ( 7 , 12 , 18 ). In the study of Ng and Yeo ( 7 ), no differences in the concentrations of test analytes were observed, while study Dimeski et al .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similarities and differences in the concentration of tested analytes measured in RST have been reported previously ( 7 , 12 , 18 ). In the study of Ng and Yeo ( 7 ), no differences in the concentrations of test analytes were observed, while study Dimeski et al .…”
Section: Discussionsupporting
confidence: 87%
“…Also, Huyghe et al . ( 18 ) observed that measured serum LD activity was significantly lower among specimens collected in RST than those collected in SST II. As the study of Parenmark and Landberg ( 19 ) showed that mixing tubes immediately after venipuncture can increase hemolysis index and that mixing blood samples after venipuncture is not mandatory for all types of tubes ( 19 , 20 ), all hemolysed samples were excluded from our study in order to prevent the influence of hemolysis, although inverting the tubes versus non inverting did not significantly affect LD activity ( 18 ).…”
Section: Discussionmentioning
confidence: 98%
“…7 In our study, samples were all collected via a cannula connector valve. Other collection factors such as incompletely filled collection tubes may also contribute to spurious potassium and LD elevations 2 ; however, specimens in our study were all collected by nursing staff trained in correct blood collection technique.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by faster clotting giving a 'more compact and robust clot, which results in less red cell disruption'. 2 Previous studies, however, were performed in settings with low rates of haemolysis (42% of samples haemolysed) 1,2 and the effect has not been evaluated where higher rates of haemolysed samples may be expected.…”
Section: Introductionmentioning
confidence: 99%
“…Adding thrombin promotes rapid clotting of the blood. An RST can be centrifuged 5 minutes after collection at 4500 rpm to provide a high-quality serum specimen, which can be sampled directly from the primary tube and can be used to measure a wide range of biochemistry parameters in routine and emergency laboratories [4,5].…”
mentioning
confidence: 99%